Philosemitism in contemporary German media. (May 2022) - Dekel, Irit
This article examines the performance of philosemitism in contemporary Germany through media representations of Jews in 2014–2020. It claims that philosemitism is practiced in Germany as a routine accomplishment of civility. It is performed in three interconnected social domains: institutional, where state institutions declare their commitment to protecting Jews as a religious minority; group, where the contingent relations between love for the Jews and exclusionary statements about them appears, mostly in casting Jews as both strange and unknown and embraced; and individual, where individuals exhibit positive sentiments toward Jews as an ideal collective, while contemplating what and who they are. It further suggests that in performing philosemitism German society examines and articulates its relations to Holocaust memory, to minorities and to the resilience of the German democracy.